2003
DOI: 10.1897/02-622
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic compounds affect development of harpacticoid copepod Tigriopus japonicus

Abstract: The aim of this investigation was to evaluate the impact of estrogenic compounds on the harpacticoid copepod Tigriopus japonicus after continuous exposure to environmentally relevant concentrations. Natural estrogen (17beta-estradiol), three known estrogenic compounds in vertebrates (bisphenol A, 4-nonylphenol, p-t-octylphenol), and an invertebrate molting hormone (20-hydroxyecdysone) were tested for their effects on development and reproductive characters in two successive generations of T. japonicus. Less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 33 publications
3
24
1
4
Order By: Relevance
“…, respectively (Andersen et al 2001;Marcial et al 2003). A significant stimulation of larval development in A. tonsa was, however, observed at 12.5-50 mg l 21 (Mariager 2001), which was also seen in our own experiments at 30 and 60 mg l…”
supporting
confidence: 81%
“…, respectively (Andersen et al 2001;Marcial et al 2003). A significant stimulation of larval development in A. tonsa was, however, observed at 12.5-50 mg l 21 (Mariager 2001), which was also seen in our own experiments at 30 and 60 mg l…”
supporting
confidence: 81%
“…Among asexual reproduction parameters, generation time or the time to release first neonate is the most sensitive resulting to an EC 50 of 1.24 mg/L (Table 2). Embryogenesis, the first stage of rotifer life cycle, is also known to be the most sensitive stage to toxicants in other zooplankters including daphnids (LeBlanc, et al, 2000) and copepods (Marcial et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Study on freshwater insect Chironomus riparius showed that adult emergence times were signiicantly delayed on moderate BPA exposure [107]. Marcial et al (2003) and Wats et al [108,109] found that the marine copepod Tigriopus japonicus showed developmental inhibition at a very low concentration of BPA (0.1 mg/L). However, it is unclear if these efects have any long-term impacts in adult life.…”
Section: Efects On Life History Traits and Developmental Eventsmentioning
confidence: 99%